Implication of Bone Mineral Density and Body Composition Parameters for Length of Hospital Stay in Patients with COVID-19 - Guan, Wenmin; Zhang, Tingting; Sun, Jing; Wei, Xuan; Wei, Wei; Yan, Ying; Song, Lijun; Qian, Husheng; Wang, Daning; Qiao, Meiqin; Liu, Guanghong; Ren, Lu; et al. (Current Medical Imaging, 2024)
Background:Multisystem information, including musculoskeletal information, can be captured from chest CT scans of patients with COVID-19 without further examination.Aims:This study aims to assess the relationship between chest CT-extracted baseline bone mineral density (BMD) and body composition parameters and the length of hospital stay in these patients.Methods:A retrospective analysis was performed in a cohort of 88 patients with COVID-19. Correlation analysis and a generalized linear model (GLM) were used to assess the associations between the length of hospital stay and covariates, including age, sex, body mass index (BMI), BMD and body composition variables.Results:The mean length of hospital stay was 27.4±8.7 days. The length of hospital stay was significantly positively associated with age (r=0.202, p=0.046) and the paraspinal muscle fat ratio (r=0.246, p=0.021). The GLM involving age, sex, BMD, paraspinal muscle fat ratio, subcutaneous adipose tissue (SAT) area, visceral adipose tissue (VAT) area, and liver fat fraction (LFF) showed that the length of hospital stay was positively correlated with VAT area (β coefficients, 95% CI: 9.304, 1.141-17.478, p=0.025).Conclusion:The musculoskeletal features extracted from chest CT correlated with the prognosis of COVID-19 patients. Factors including old age, a higher paraspinal muscle fat ratio and a larger VAT area in patients with COVID-19 were associated with longer hospital stays.
Keywords: Visceral fat